A phase I study of FCN-411, a pan-HER inhibitor, in EGFR-mutated advanced NSCLC after progression on EGFR tyrosine kinase inhibitors. (April 2022) - Lin, Lin; Pan, Hongming; Li, Xingya; Zhao, Chengling; Sun, Jiangtao; Hu, Xingsheng; Zhang, Yiping; Wang, Mengzhao; Ren, Xiubao; Luo, Xiaoyong; Shan, Guoyong; Hui, Ai-Min; et al.
Highlights: FCN-411 had a manageable safety profile. FCN-411 showed antitumor activity in EGFR TKI-treated, EGFR -mutated advanced NSCLC. Patients without EGFR T790M achieved a greater ORR than those with this mutation. Abstract: Background: There are no approved epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) for EGFR -mutated non-small cell lung cancer (NSCLC) without EGFR T790M mutation after progression on first- or second-generation EGFR-TKIs. Methods: We conducted this phase I, open-label, multicenter, dose-escalation/dose-expansion study to evaluate the safety, tolerability, antitumor activity, and pharmacokinetics of FCN-411, a TKI targeting EGFR, HER2, and HER4, in patients with EGFR -mutated advanced NSCLC whose disease had progressed during treatment of EGFR-TKIs. Adult patients with stage IIIB–IV NSCLC harboring EGFR mutations (exon 18/19/20/21) who had progressed on prior EGFR-TKIs were enrolled. In the dose-escalation phase, patients received 4 mg, 8 mg, 12 mg, and 16 mg FCN-411 once daily until the maximum tolerated dose (MTD). In the dose-expansion phase, patients received FCN-411 at the recommended phase II dose (RP2D) continuously in 21-day cycles. The primary endpoints were safety, tolerability, MTD, and RP2D. Results: From July 23, 2018 to September 29, 2020, 77 patients were enrolled, including 30 with EGFR T790M mutation in tumor tissues. The cut-off date was February 1, 2021. No dose-limiting toxicities were observed. The most common grade ≥ 3 treatment-emergent adverse events among all patients were diarrhea (8; 10.4%) and dermatitis acneiform (7; 9.1%). Ten of 67 evaluable patients achieved confirmed partial response, with an objective response rate (ORR) of 14.9% (95% confidence interval [CI], 8.3–24.0); the ORR was 33.3%, 14.0%, 0, and 25.0% at 4 mg, 8 mg, 12 mg, and 16 mg, respectively. Besides, the ORR in patients without and with EGFR T790M mutation was 20.5% and 7.4%, respectively. Moreover, 39 patients achieved stable disease across all doses, and the disease control rate was 73.1% (95% CI, 60.9–83.2). Median progression-free survival was 4.1 (95% CI, 2.9–5.3) months. Median duration of response and overall survival have not been reached. Conclusions: FCN-411 was well tolerated and demonstrated preliminary antitumor activity in patients with EGFR -mutated NSCLC after progression on EGFR-TKIs, especially in those without EGFR T790M mutation. The RP2D was defined as 8 mg once daily. Future studies are warranted. Trial registration: ClinicalTrials.gov, NCT03420079.